Foliage covered parade float - Gordon, John C. (photographer):::Creator::::::::::::
Photograph shows a man driving a foliage covered parade float for the California Prune and Apricot Growers. A large letter "S" representing the Sunsweet Brand of prunes and apricot is the centerpiece of the float. Painted on the tall building in the background is a sign that reads, "The Park Furnished Rooms and Apartments."